Empowerment of Diabetes Self-Management Assistance Groups (DAG) as an Effort to Improve Self Care Behavior of Diabetes Mellitus Patients in Gorontalo City - Syamsidar Syamsidar; Fakhriatul Falah (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Self-care management is the key to the success of diabetes mellitus treatment. Self-care of glucose management, diet control, a healthy lifestyle will determine quality of life of people with Diabetes Mellitus, but it can’t be achieved without support from patients environment, included family. .Therefore, this community service activity is expected to be able to increase the knowledge, skills, and abilities of families in carrying out independent care for family members who suffer from Diabetes Mellitus, improve self care behavior in Diabetes Mellitus Patients so that the health status of people with Diabetes Mellitus in the Gorontalo City can be increased. In addition to involving the family, health cadres as part of the community also play a role in efforts to improve the health quality of Diabetes Mellitus Patients by increasing their understanding and skills in treating Diabetes Mellitus Patients. This Community Service begins with the formation of Diabetes Assistance Group (DAG) , improving the basic competencies of health cadres and families through structured education and training, followed by monitoring and evaluation of the DAG programme. The results obtained showed an increase in the posttest knowledge average in 10 health cadres who had been given education and a decrease in blood glucose levels in 30 diabetes patient who became the fostered family with an average decrease of 111 mg/dL.